Spatial framing in tourism advertising: the linguistic construction of exoticism in Indonesian destination campaigns - Pandu Hidayat (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Tourism advertising in Indonesia not only promotes destinations but also constructs spatial and cultural imaginaries that influence global perceptions and local policies. Objective: This study aims to examine how Indonesian tourism campaigns linguistically and visually frame destinations as “exotic,” “authentic,” and “pristine,” and to uncover the ideological narratives embedded in these representations. Method: Using a qualitative multimodal discourse analysis framework that integrates Spatial Discourse Analysis, Barthesian semiotics, and Critical Discourse Analysis, the research analyzes national promotional videos, regional brochures, and official social media content from 2020–2023. Results: The findings reveal that linguistic framings rely heavily on spatial metaphors (“hidden paradise,” “beyond the ordinary”) paired with sweeping visuals to evoke remoteness and exclusivity; visual exoticism is constructed through saturated color palettes, traditional costumes, and symmetrical compositions that aestheticize culture; and ideological narratives reproduce a curated tourist gaze that privileges external audiences while marginalizing local agency. Implication: The study implies that policymakers and tourism marketers should adopt more inclusive and context-sensitive approaches that balance promotional appeal with authenticity, community agency, and sustainability. Novelty: This study shows how multimodal tourism discourses construct spatial imaginaries that simultaneously enhance nation branding while reproducing selective representations that marginalize local agency and cultural complexity.